2015
DOI: 10.1093/scan/nsu166
|View full text |Cite
|
Sign up to set email alerts
|

Distress of ostracism: oxytocin receptor gene polymorphism confers sensitivity to social exclusion

Abstract: A single-nucleotide polymorphism on the oxytocin receptor gene (OXTR), rs53576, involving a guanine (G) to adenine (A) substitution has been associated with altered prosocial features. Specifically, individuals with the GG genotype (i.e. the absence of the polymorphism) display beneficial traits including enhanced trust, empathy and self-esteem. However, because G carriers might also be more socially sensitive, this may render them more vulnerable to the adverse effects of a negative social stressor. The curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…Among G allele carriers this association was mediated by subjective ratings of interpersonal distrust. Support for this higher sensitivity to a dysfunctional or stressful social environment in rs53576 G allele carriers was further substantiated by both observational (Burkhouse et al, 2015; Dannlowski et al, 2015; Hostinar et al, 2014; Smearman et al, 2015; Sturge-Apple et al, 2012; Windle and Mrug, 2015) and experimental studies (Chen et al, 2011; McQuaid et al, 2015; Norman et al, 2012). As examples of observational studies, it could be shown that rs53576 GG homozygous subjects with ELS exposure have a smaller bilateral volume of the ventral striatum, a key structure of the dopaminergic nigrostriatal pathway (Dannlowski et al, 2015) which is implicated in both depression risk (Nestler and Carlezon, 2006) and parenting behavior (Strathearn et al, 2009).…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 89%
See 1 more Smart Citation
“…Among G allele carriers this association was mediated by subjective ratings of interpersonal distrust. Support for this higher sensitivity to a dysfunctional or stressful social environment in rs53576 G allele carriers was further substantiated by both observational (Burkhouse et al, 2015; Dannlowski et al, 2015; Hostinar et al, 2014; Smearman et al, 2015; Sturge-Apple et al, 2012; Windle and Mrug, 2015) and experimental studies (Chen et al, 2011; McQuaid et al, 2015; Norman et al, 2012). As examples of observational studies, it could be shown that rs53576 GG homozygous subjects with ELS exposure have a smaller bilateral volume of the ventral striatum, a key structure of the dopaminergic nigrostriatal pathway (Dannlowski et al, 2015) which is implicated in both depression risk (Nestler and Carlezon, 2006) and parenting behavior (Strathearn et al, 2009).…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 89%
“…Men carrying the G allele were more likely to exhibit an attenuated cortisol response to a public speaking challenge when receiving social support (Chen et al, 2011), whereas A allele homozygotes appeared to be resistant to the stress-buffering effect of social support. Finally, in an experimental manipulation of social exclusion, only G allele homozygous women reported reduced self-esteem compared to participants who were not excluded, indicating a higher rejection sensitivity in GG women (McQuaid et al, 2015). Concordantly, excluded GG carriers’ systolic blood pressure remained elevated during the game and 30 minutes thereafter, and excluded GG carriers also had higher cortisol levels than included GG individuals.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 90%
“…Some of these effects of MDMA may be mediated through the release of oxytocin, and so OXTR variation may also contribute to individual differences in the therapeutic efficacy of the drug. While one recent study found that A/A individuals may be less sensitive to social ostracism (McQuaid, McInnis, Matheson, & Anisman, 2015), they may also be less likely to derive psychological benefits from social support in general. These individuals are less likely to seek social support (Kim et al, 2010), and for A/A homozygotes, social support during stress does not reduce cortisol responses (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whereas the rs53576 OXT receptor polymorphism is associated with emotional support seeking in Americans, it is not in Koreans28. This same polymorphism is also associated with differential responses to social stress29 and social exclusion30.…”
mentioning
confidence: 99%
“…In this paradigm subjects play a ball tossing game with players via the internet who either exclude or include them during the game and, unbeknownst to them, are actually computer controlled31. Two studies have shown that plasma OXT concentrations rise significantly in healthy controls, but not in Borderline Personality disorder or depression patients, after the experience of being excluded in this game3233 and another found an association between the rs53576 (G-carriers) polymorphism of the OXT receptor gene and emotional responses to exclusion in the game30. One study has reported that intranasal OXT promoted prosocial behavior towards a victim of social rejection in individuals who experienced low levels of maternal love withdrawal34.…”
mentioning
confidence: 99%